2008
DOI: 10.1177/0011000007309966
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Work

Abstract: Because of recent advances in medications and treatment regimens, persons with HIV disease are maintaining better health status and living longer. Thus, greater opportunities exist for these individuals to either continue their current employment or return to the world of work. The purpose of this qualitative study was to provide in-depth descriptions of related vocational experiences of persons with HIV. Data were collected from eight focus groups consisting of a diverse sample of people living with HIV (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Based on our findings and current literature on HIV in the workplace, we recommend specialized vocational counseling services for PLWH (Degroote et al, 2014;Worthington et al, 2012). Such counseling could provide guidance with respect to disclosure decisions (Maguire et al, 2008;Worthington et al, 2012). We recommend that these services emphasize that disclosure of HIV status at work is a choice, even in the health care sector (Chaudoir et al, 2011;Henry et al, 2015).…”
Section: Implications and Recommendationsmentioning
confidence: 84%
See 3 more Smart Citations
“…Based on our findings and current literature on HIV in the workplace, we recommend specialized vocational counseling services for PLWH (Degroote et al, 2014;Worthington et al, 2012). Such counseling could provide guidance with respect to disclosure decisions (Maguire et al, 2008;Worthington et al, 2012). We recommend that these services emphasize that disclosure of HIV status at work is a choice, even in the health care sector (Chaudoir et al, 2011;Henry et al, 2015).…”
Section: Implications and Recommendationsmentioning
confidence: 84%
“…Also, fears of ''being discovered'' at work and the corresponding cognitive burden of concealment reported by participants in our study have been documented in the extensive literature on concealing stigmatized identities (Chaudoir et al, 2011;Pachankis, 2007) and in studies on disclosure or concealment at work (Braveman, Levin, Kielhofner, & Finlayson, 2006). For example, in a grounded theory study with 93 PLWH living in the United States (Maguire et al, 2008), participants reported anxiety about concealing and hypervigilant behaviors to maintain concealment at work.…”
Section: Disclosure or Concealment At Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma is particularly felt among individuals living with HIV for four reasons: (a) HIV is often viewed as the bearer's responsibility; (b) HIV is seen as permanent and fatal; (c) HIV is contagious; and (d) HIV is sometimes accompanied by physical changes, especially for individuals with AIDS (Brown, Macintyre, & Trujillo, 2003). For PLWHA, the presence of HIV-related stigma, or societal disapproval geared at PLWHA, directly affects quality of life (Maguire et al, 2008). Furthermore, stigma serves as a complicating barrier toward providing effective services to individuals living with HIV, and it often undermines the work mental health professionals are doing to treat clients (Brown et al, 2003;Steward et al, 2008).…”
mentioning
confidence: 99%